2019
DOI: 10.1098/rspb.2019.1675
|View full text |Cite
|
Sign up to set email alerts
|

Post-copulatory sexual selection allows females to alleviate the fitness costs incurred when mating with senescing males

Abstract: Male senescence has detrimental effects on reproductive success and offspring fitness. When females mate with multiple males during the same reproductive bout, post-copulatory sexual selection that operates either through sperm competition or cryptic female choice might allow females to skew fertilization success towards young males and as such limit the fitness costs incurred when eggs are fertilized by senescing males. Here, we experimentally tested this hypothesis. We artificially inseminated female North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 42 publications
3
40
3
Order By: Relevance
“…The diversity of parameters affected by senescence is consistent with studies in other vertebrate species, where senescence has been shown to affect sperm quality and quantity in males, such as in red wolf Canis rupus 6 and Pelvicachromis taeniatus 23 ; female juvenile production, such as in Accipiter nisus 65 and great tit Parus major 66 ; or the brood size of females, such as in great tit Parus major 66 . The results corroborate those of previous studies in houbara conducted in captivity at the phenotypic level 38 40 and the genetic level 37 . In addition, a recent study of the reproductive parameters of captive-bred individuals released into the wild showed that the deleterious effects of senescence translated into free-ranging population reproductive success parameters, such as nest survival (i.e., the probability that at least one egg remains in the nest at a given time interval) or clutch size 36 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The diversity of parameters affected by senescence is consistent with studies in other vertebrate species, where senescence has been shown to affect sperm quality and quantity in males, such as in red wolf Canis rupus 6 and Pelvicachromis taeniatus 23 ; female juvenile production, such as in Accipiter nisus 65 and great tit Parus major 66 ; or the brood size of females, such as in great tit Parus major 66 . The results corroborate those of previous studies in houbara conducted in captivity at the phenotypic level 38 40 and the genetic level 37 . In addition, a recent study of the reproductive parameters of captive-bred individuals released into the wild showed that the deleterious effects of senescence translated into free-ranging population reproductive success parameters, such as nest survival (i.e., the probability that at least one egg remains in the nest at a given time interval) or clutch size 36 .…”
Section: Discussionsupporting
confidence: 91%
“…The study model was a large captive population of North African houbara bustard Chlamydotis undulata undulata (Jacquin 1784, hereafter houbara) that have been maintained in captivity and managed to maximize the maintenance of genetic diversity for 24 years 31 , 32 . Our study is at the interface of previous research on houbara that have highlighted (1) a negative effect of inbreeding on behavioral phenotypes 33 , 34 , hatching success, post hatching mortality and growth 35 ; (2) the senescence of reproductive parameters in the free-ranging population 36 but also in the captive population 37 40 ; (3) the efficient maintenance of genetic diversity and minimization of inbreeding within the captive population 32 ; and (4) intergenerational variations in reproductive parameters 41 , 42 . Within this framework, we were particularly interested in (1) quantifying the relative effects of age, inbreeding and number of generations in captivity on reproductive performance and (2) assessing their potential interactions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Later, Albert Lansing’s work on parthenogenic rotifers 13,14 (see also 15 ) showed that selection lines propagated through older parents gave rise to shorter-lived offspring and went extinct faster than selection lines using young parents. Subsequent studies have confirmed that offspring of older mothers may have reduced lifespan in a wide range of taxa, including flies 5,16 , nematodes 2 , butterflies 17 , water fleas 18 , birds 1922 , mice 23 , squirrels 24 and humans 25 . The lifespan reduction in offspring of older parents led Lansing to suggest that age-dependent changes, or an ‘ageing factor’, is passed on to offspring of older parents, shortening the lives of those offspring – now commonly referred to as the Lansing effect.…”
Section: Introductionmentioning
confidence: 95%
“…In houbara bustards Chlamydotis undulata, for example, the use of sperm from older males in IVF trials gave rise to reduced hatching success and slower growing offspring [153,154]. However, the sperm of younger males was found to either outcompete that of older males or to be preferentially selected by females [154]. Surprisingly, sperm from immature males produced the fastest growing offspring [153]; this raises the question as to why such males still behave as if they are immature when their sperm appear to be of particularly high quality, but it could relate to the costs of competition with other males.…”
Section: Implications For Life Historiesmentioning
confidence: 99%